Facilitators and barriers of breastfeeding late preterm infants according to mothers' experiences. Issue 1 (December 2016) - Giannì, Maria; Bezze, Elena; Sannino, Patrizio; Stori, Elena; Plevani, Laura; Roggero, Paola; Agosti, Massimo; Mosca, Fabio
Abstract Background Late preterm infants account for the majority of preterm births. They are at an increased risk of neonatal mortality and morbidity and are less likely to initiate breastfeeding and to be exclusively breastfed at discharge compared to infants born at term. The aim of this study was to identify the facilitators and barriers to breastfeeding during hospital stays according to the experiences of mothers of late preterm infants. Methods We conducted a cross-sectional questionnaire survey. Mothers who intended to breastfeed and had given birth to a newborn admitted to level I and II care, with a gestational age of 34 0/7 to 36 6/7 weeks, were enrolled. Sociodemographic data, neonatal variables, mode of feeding and feeding status at discharge were also collected. Results A total of 92 mothers who had given birth to 121 infants were enrolled. At discharge, any human milk was fed to 94 % of infants, with exclusively human milk being fed in 43 % of cases; exclusively formula was fed to 6 % of infants. In the multivariate analysis, having expressed breast milk was independently associated with an increased risk of being fed with either any human milk or formula only (OR = 2.73, 95 % CI 1.05–7.1, p  = 0.039), whereas being encouraged to practice kangaroo mother care tended to have a protective effect (OR = 0.46, 95 % CI 0.2–1.06, p  = 0.07). Conclusions Based on the present findings, health care professionals should strive to fully implement breastfeeding support for mothers of late preterm infants who intend to breastfeed, in particular optimizing breast milk expression and promoting kangaroo mother care. Further studies are needed to gain further insight into the complex interplay of the factors that modulate breastfeeding outcome in late preterm infants.